Constrained space-time zero-forcing pre-equalizer for the downlink channel of UMTS-TDD - Morgado, A.
The great diversity of services expected to be delivered by third generation mobile radio systems will impose severe operating conditions on the mobile terminal in terms of computational requirements and power consumption. Therefore, in this work we propose to move the most demanding signal precessing tasks, usually performed by the mobile unit, to the base station. This technique is developed here for a UMTS-TDD downlink scenario through an equalizer synthesis method based on the redundancy between non-overlapping bands of a Direct Sequence Spread Spectrum (DS-SS) signal, with the design optimised for minimum power transmission under the zero-forcing criterion.